2023
DOI: 10.3390/drones7020070
|View full text |Cite
|
Sign up to set email alerts
|

An Effective Approach for Automatic River Features Extraction Using High-Resolution UAV Imagery

Abstract: The effects of climate change are causing an increase in the frequency and extent of natural disasters. Because of their morphological characteristics, rivers can cause major flooding events. Indeed, they can be subjected to variations in discharge in response to heavy rainfall and riverbank failures. Among the emerging methodologies that address the monitoring of river flooding, those that include the combination of Unmanned Aerial Vehicle (UAV) and photogrammetric techniques (i.e., Structure from Motion-SfM)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 52 publications
0
8
0
Order By: Relevance
“…They found that depending on when the orthomosaic was collected, either the random forest or k-Nearest Neighbors performed the best in terms of the f1-score [3]. However, Noi and Kappas [4] showed that support vector machines outperformed both random forest and k-nearest neighbors when classifying features from Sentinel-2 imagery.…”
Section: Background 21 Automatic Watercourse Extraction Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that depending on when the orthomosaic was collected, either the random forest or k-Nearest Neighbors performed the best in terms of the f1-score [3]. However, Noi and Kappas [4] showed that support vector machines outperformed both random forest and k-nearest neighbors when classifying features from Sentinel-2 imagery.…”
Section: Background 21 Automatic Watercourse Extraction Methodsmentioning
confidence: 99%
“…Existing datasets of small watercourses are often lacking in both completeness and accuracy. However, as new high-resolution remote-sensing datasets have emerged, there has been increased research on automated and semi-automatic methods for the extraction of watercourses [1][2][3][4][5]. Convolutional neural networks (CNNs) are state-of-the-art networks for computer vision tasks [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…Examples of significant events with a declared state of emergency that occurred in the Basilicata Region in the last ten years are listed in Table 1. These events led the scientific community to develop relevant research for landslide characterization [20,22,25,26] and flood monitoring, vulnerability and risk mapping [24,[27][28][29][30][31][32][33]. In terms of national and regional hazard data, Figure 1 shows the spatial distribution of the landslide and flood hazard in the Basilicata Region, derived from Italian Institute for Environmental Research and Protection (ISPRA) 2020-2021 mosaic layers.…”
Section: Multi-hazard Context In the Basilicata Regionmentioning
confidence: 99%
“…UAVs are especially vital in scenarios involving peril, such as natural disasters. Various solutions have been developed to aid in locating individuals affected by earthquakes, building collapses, or river floods [11][12][13][14][15][16]. While these solutions use cameras to detect specific objects, they primarily focus on object identification within images, which can vary in size depending on the object being sought.…”
Section: Related Workmentioning
confidence: 99%